Evaluasi Pengelolaan Limbah Bahan Berbahaya dan Beracun (B3) di PT. X - Siti Amalia Fajriyah; Eka Wardhani (Jurnal Serambi Engineering, 2020)
Disposal of the residual production of an industry containing hazardous and toxic materials can have a negative impact on the environment and human health. PT. X The Spinning Division is a company engaged in spinning yarn that produces hazardous waste in the production process, especially in machine maintenance. The hazardous waste produced is in the form of used TL lamps, contaminated cotton waste, used oil, and used hazardous packaging. The hazardous waste is toxic, corrosive and flammable. The purpose of this study is to compare the existing conditions of hazardous waste management with applicable regulations. The study was conducted by directly observing the existing conditions and scoring using Guttman scale. The research variables include sorting, storing, collecting, transporting, utilizing, processing and landfill hazardous waste. The results showed that the management of hazardous waste in PT. X The Spinning Division gets a score 34.3% which is categorized “Poor”.